GLP1R boosts survival, migration and invasion of endometrial cancer cells and protects against ferroptotic cell death - Wu Li; Wen Lyu; Songjun Liu; Fan Ruan; Xinmei Zhang (Journal of Obstetrics and Gynaecology)
Background Despite the strong evidence concerning carcinogenic roles of glucagon-like peptide 1 receptor (GLP1R), the role of this gene in endometrial cancer (EC) remains elusive. This study investigated the properties of GLP1R on EC in vitro.Methods The expression of GLP1R in EC was detected by RT-qPCR, immunohistochemistry, and western blotting. Cell viability, cell cycle, apoptosis, migration, invasion and ferroptosis were assessed through CCK-8, flow cytometry, wound healing, transwell, DCFH-DA and western blotting, respectively.Results We found that GLP1R was up-regulated in EC than normal specimens. It had the highest expression in AN3CA cells. Cell viability, migration and invasion were significantly reduced, while cell cycle arrest and apoptosis were induced following GLP1R knockdown. The malignant biological behaviours of AN3CA cells were investigated when treated with exendin-4 (GLP1R agonist). Moreover, GLP1R lowered intracellular ROS level and expression of SLC7A11, and FTH1, but mitigated GPX4 expression in AN3CA cells.Conclusion In a word, GLP1R was up-regulated in EC and its up-regulation facilitated the proliferative and metastatic potentials, and protected cells from ferroptosis, thereby accelerating EC progression. These data emphasised the potency of GLP1R as a therapeutic agent against EC.